Variations at regulatory regions of the milk protein genes are associated with milk traits and coagulation properties in the Sarda sheep. (20th July 2016) - Noce, A.; Pazzola, M.; Dettori, M. L.; Amills, M.; Castelló, A.; Cecchinato, A.; Bittante, G.; Vacca, G. M.
Summary: Regulatory variation at the ovine casein genes could have important effects on the composition and coagulation properties of milk. Herewith, we have partially resequenced the promoters and the 3′‐UTR of the four casein genes in 25 Sarda sheep. Alignment of these sequences allowed us to identify a total of 29 SNPs. This level of polymorphism (one SNP every 250 bp) is remarkably high if compared with SNP densities estimated in human genic regions (approximately one SNP per bp). The 29 SNPs identified in our resequencing experiment, plus three previously reported SNPs mapping to the lactalbumin, alpha ( LALBA ) and β‐lactoglobulin ( BLG, also known as progestagen‐associated endometrial protein, PAEP ) genes, were genotyped with a multiplex TaqMan Open Array Real‐Time PCR assay in 760 Sarda sheep with records for milk composition and coagulation properties. Association analysis revealed the existence of significant associations of CSN1S2 and CSN3 genotypes with milk protein and casein contents. Moreover, genotypes at CSN1S1 were significantly associated with rennet coagulation time, curd firming time and curd firmness, whereas CSN2 was associated with curd firming time. These results suggest that SNPs mapping to the promoters and 3′‐UTRs of ovine casein genes may exert regulatory effects on gene expression and that they could be used for improving sheep milk quality and technological traits at the population level through marker assisted selection.